Thermophysical optimization of specialized concrete pavement materials for collection of surface heat energy and applications for shallow heat storage - Dehdezi, Pejman Keikhaei; Hall, Matthew R.; Dawson, Andrew (National Academy of Sciences, 2011)
There is great potential to use pavement structures to collect and/or store solar energy for the heating and cooling of adjacent buildings, e.g. airport terminals, shopping malls, etc. Therefore, pavement materials comprising both conventional and unconventional concrete mixtures with a wide range of densities, thermal conductivities, specific heat capacities, and thermal diffusivities were investigated. Their thermo-physical properties were then used as inputs to a one dimensional transient heat transport model in order to evaluate the temperature changes at the various depths at which heat might be abstracted or stored. The results indicated that a high diffusivity pavement, e.g. incorporating high conductive aggregates and/or metallic fibres, can significantly enhance heat transfer as well as reduction of thermal stresses across the concrete slab. On the other hand a low diffusivity concrete can induce a more stable temperature at shallower depth enabling easier heat storage in the pavement as well as helping to reduce the risk of damage due to freeze-thaw cycling in cold regions.